Calculation of the temperature integ rals used in the processing of t he r mogravimetric analysis data (2019)
(Eng) There is no standard procedure for calculating the generalized temperature integral, instead myriads of different approximations to it are applied in the processing of thermogravimetric analysis data. This work presents first an integration procedure based on the Simpson rule that generates reference values of the generalized temperature integral. It also reviews the available representations of the temperature integral in power series, and presents the conversion of its generalized form into the form of sp ecial functions. From the comparison with the reference values from integration it was concluded that for argument values of practical interest the generalized temperature integral is best computed as the incomplete gamma function.